Old Norse studies in Poland. History and perspectives - Jakub Morawiec (Fasciculi Archaeologiae Historicae, 2015)
History of Old Norse studies in Poland consists of two main elements: attempts to use sagas, especially kings’ sagas as valuable addition to source data in research on early medieval Poland and Scandinavia and literary studies connected with saga translations in Polish and promotion of the genre among both professional and general audience. Both strands are continued. What makes the present perspective different from the past on is the fact, that one can talk about more coherent research, including both literary and historical aspects. Besides, this research, still with prospects to develop, has much more advanced international approach. Thus being important addition to medieval studies in Poland.